Resources Use Efficiency in Agriculture - Kumar, Sandeep; Meena, Ram Swaroop; Jhariya, Manoj Kumar; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2020)
Achieving zero hunger and food security is a top priority in the United Nations Development Goals (UNDGs). In an era characterized by high population growth and increasing pressure on agricultural systems, efficiency in the use of natural resources has become central to sustainable agricultural practices. Fundamentally speaking, eco-efficiency is about maximizing agricultural outputs, in terms of quantity and quality, using less land, water, nutrients, energy, labor, or capital. The concept of eco-efficiency involves both the ecological and economic aspects of sustainable agriculture. It is therefore essential to understand the interaction of ecosystem constituents within the extensive agricultural landscape, as well as farmers' economic needs. This book examines the latest eco-efficient practices used in agro-systems. Drawing upon research and examples from around the world, it offers an up-to-date overview, together with insights into directly applicable approaches for poly-cropping systems and landscape-scale management to improve the stability of agricultural production systems, helping achieve food security. The book will be of interest to educators, researchers, climate change scientists, capacity builders and policymakers alike. It can also be used as additional reading material for undergraduate and graduate courses on agriculture, forestry, soil science, and the environmental sciences.
Chapter 1: Waste recycling for the Eco-friendly Input Use Efficiency in Agriculture -- Chapter 2: Earthworms for Eco-friendly Resource Efficient Agriculture -- Chapter 3: Biopesticides for Agriculture and Environment Sustainability -- Chapter 4: Precision Agriculture for Resource Use Efficiency -- Chapter 5: Nanomaterials for Agriculture Input Use Efficiency -- Chapter 6: Solar Radiation and Nitrogen Use Efficiency for Sustainable Agriculture -- Chapter 7: Nitrogen and Phosphorus Use Efficiency in Agroecosystems -- Chapter 8: Long-Term Impact of Fertilizers on Soil and Rice Productivity -- Chapter 9: Organic Sources and Tillage Practices for Soil Management -- Chapter 10: Technical Efficiency in Agriculture -- Chapter 11: Agrochemicals Impact on Ecosystem and Bio-monitoring -- Chapter 12: Plant Biotechnology for Agricultural Sustainability -- Chapter 13: Soil and Water Conservation Measures for Mediterranean Fruit Crops in Rainfed Hillslopes -- Chapter 14: Efficient Use of Soil in Silvopastoral Systems of Native Forests -- Chapter 15: Water Resource and Use Efficiency under Changing Climate -- Chapter 16: Recovery of Micronutrients in Alkaline Soils: Recent Challenges and Future Perspectives -- Chapter 17: Biofortification of Cereals with Zn and Fe: Recent Advances and Future Perspectives -- Chapter 18: Resources Management for Sustainable Sugarcane Production -- Chapter 19: Linking Sustainability and Competitiveness of Almond Plantations under Water Scarcity and Changing Climate -- Chapter 20: Efficiently Groundcovers in Mediterranean Olive Groves under Changing Climate.
Keywords: Agriculture; Ecosystems; Plant physiology; Plant anatomy; Plant development; Agriculture; Ecosystems; Plant Physiology; Plant Anatomy/Development.